Detailed Sensory Memory, Sloppy Working Memory - Sligte, Ilja G.; Vandenbroucke, Annelinde R.; Scholte, H.Steven; Lamme, Victor (Frontiers in Psychology, 2010)
Visual short-term memory (VSTM) enables us to actively maintain information in mind for a brief period of time after stimulus disappearance. According to recent studies, VSTM consists of three stages – iconic memory, fragile VSTM, and visual working memory – with increasingly stricter capacity limits and progressively longer lifetimes. Still, the resolution (or amount of visual detail) of each VSTM stage has remained unexplored and we test this in the present study. We presented people with a change detection task that measures the capacity of all three forms of VSTM, and we added an identification display after each change trial that required people to identify the “pre-change” object. Accurate change detection plus pre-change identification requires subjects to have a high-resolution representation of the “pre-change” object, whereas change detection or identification only can be based on the hunch that something has changed, without exactly knowing what was presented before. We observed that people maintained 6.1 objects in iconic memory, 4.6 objects in fragile VSTM, and 2.1 objects in visual working memory. Moreover, when people detected the change, they could also identify the pre-change object on 88% of the iconic memory trials, on 71% of the fragile VSTM trials and merely on 53% of the visual working memory trials. This suggests that people maintain many high-resolution representations in iconic memory and fragile VSTM, but only one high-resolution object representation in visual working memory.